Management of Salivary Gland Malignancy: ASCO Guideline. Issue 17 (10th June 2021) - Geiger, Jessica L.; Ismaila, Nofisat; Beadle, Beth; Caudell, Jimmy J.; Chau, Nicole; Deschler, Daniel; Glastonbury, Christine; Kaufman, Marnie; Lamarre, Eric; Lau, Harold Y.; Licitra, Lisa; Moore, Michael G.; et al.
Abstract : PURPOSE: To provide evidence-based recommendations for practicing physicians and other healthcare providers on the management of salivary gland malignancy. METHODS: ASCO convened an Expert Panel of medical oncology, surgical oncology, radiation oncology, neuroradiology, pathology, and patient advocacy experts to conduct a literature search, which included systematic reviews, meta-analyses, randomized controlled trials, and prospective and retrospective comparative observational studies published from 2000 through 2020. Outcomes of interest included survival, diagnostic accuracy, disease recurrence, and quality of life. Expert Panel members used available evidence and informal consensus to develop evidence-based guideline recommendations. RESULTS: The literature search identified 293 relevant studies to inform the evidence base for this guideline. Six main clinical questions were addressed, which included subquestions on preoperative evaluations, surgical diagnostic and therapeutic procedures, appropriate radiotherapy techniques, the role of systemic therapy, and follow-up evaluations. RECOMMENDATIONS: When possible, evidence-based recommendations were developed to address the diagnosis and appropriate preoperative evaluations for patients with a salivary gland malignancy, therapeutic procedures, and appropriate treatment options in various salivary gland histologies. Additional information is available at www.asco.org/head-neck-cancer-guidelines .